Physiological and performance monitoring in competitive sporting environments: A review for elite individual sports - Kiely, M.; Warrington, G.; McGoldrick, A.; Cullen, S. J. (Strength and Conditioning Journal, 2019)
There is a great appreciation for the application of physiological monitoring within competition for individual sports. Physiological monitoring allows feedback on exercise dose-response, exercise intensity, and exercise performance. Both subjective and objective parameters are commonly measured in the field sports, but research investigating the accuracy and applicability of monitoring tools in a competitive environment for individual athletes is limited. This narrative review highlights the strengths and weaknesses of individual devices to measure a variety of parameters, including physiological performance, and biochemical and subjective parameters. Based on an analysis of the existing scientific literature, practical applications are provided for coaches.